2016
DOI: 10.3847/0004-637x/828/1/62
|View full text |Cite
|
Sign up to set email alerts
|

How Did a Major Confined Flare Occur in Super Solar Active Region 12192?

Abstract: We study the physical mechanism of a major X-class solar flare that occurred in the super NOAA active region (AR) 12192 using a data-driven numerical magnetohydrodynamic (MHD) modeling complemented with observations. With the evolving magnetic fields observed at the solar surface as bottom boundary input, we drive an MHD system to evolve self-consistently in correspondence with the realistic coronal evolution. During a two-day time interval, the modeled coronal field has been slowly stressed by the photospheri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 86 publications
7
63
0
1
Order By: Relevance
“…Importantly, the absence of photospheric-flux cancellation underlying the post-flare loops associated with the non-eruptive flares confirms that there were no converging motions of the foot points of opposite magnetic polarities which can result in photospheric foot-point reconnection along the PIL to form the flux rope. These observations support the idea of tether-cutting reconnection reported by Chen et al (2015) and Jiang et al (2016). They considered the shearing motion of the photospheric fluxes to be responsible for stressing the coronal magnetic field and building up a large current sheet that triggered the magnetic reconnection and produced the homologous high energetic flares.…”
Section: Magnetic-field Evolution For the Non-eruptive Flaressupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, the absence of photospheric-flux cancellation underlying the post-flare loops associated with the non-eruptive flares confirms that there were no converging motions of the foot points of opposite magnetic polarities which can result in photospheric foot-point reconnection along the PIL to form the flux rope. These observations support the idea of tether-cutting reconnection reported by Chen et al (2015) and Jiang et al (2016). They considered the shearing motion of the photospheric fluxes to be responsible for stressing the coronal magnetic field and building up a large current sheet that triggered the magnetic reconnection and produced the homologous high energetic flares.…”
Section: Magnetic-field Evolution For the Non-eruptive Flaressupporting
confidence: 85%
“…However, from a study of flare-CME association rate it was found that 75 % of GOES flare ≥ X1.0 class are CME productive, and for the flare class ≥ X2.5 the CME association rate is more than 90 % (Yashiro et al, 2006). Thus the flare-rich but CME-poor AR 12192 drew considerable attention from the solar community (Sun et al, 2015;Chen et al, 2015;Thalmann et al, 2015;Liu et al, 2016;Jiang et al, 2016). AR 12192 crossed the visible solar disc from 17 to 30 October 2014 and produced 6 X-class flares, 22 M-class flares, and 53 C-class flares.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon is often explained by the authors exploiting the implosion conjecture, because this predicts a more horizontal field as loops contract, which could probably propagate from the restructuring corona down to the photosphere during the impulsive phase (Hudson et al 2008;Fisher et al 2012). However, the non-eruptive X3.1 flare in the famous active region 12192 did not show significant changes in its photospheric horizontal field (Sun et al 2015;Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is fair to mention that this AR is rather unusual as being extremely large but, interestingly, CME-poor. AR 12192 has been described well in the literature (Veronig & Polanec, 2015;Jiang et al, 2016;Liu et al, 2016). Here, again, we notice the fol-lowing remarkable properties of the W G M and the distance.…”
Section: Discussionmentioning
confidence: 76%